COMPREHENSIVE ANALYSIS OF GROUNDWATER QUALITY IN BANTAYAN VILLAGE TOURISM AREA, NORTH ACEH: PHYSICAL, CHEMICAL, AND MICROBIOLOGICAL PERSPECTIVES - Syafrizal, Syafrizal; Sari, Arlin Maya; Dewi, Ucia Mahya; Nasution, Nurul Azmi; Fadillah, Putri (FKIP USK, 2024)
The water quality of drilled wells in the tourist area of Bantayan village, North Aceh, has been carried out. This study aims to find out how suitable the water from the drilled well is for use by the community in the area. Samples were taken from five water sources of drilled wells with a depth of 3.5 m located in Bantayan village. The feasibility of water consumption can be assessed by testing the quality based on microbiological, physical, and chemical parameters. The parameters measured were color, turbidity, odor (physics), heavy metal content pH (chemical), and bacterial content (microbiology). The measurement results showed that although almost all water samples had water quality that met the standards based on physical and chemical parameters, the water sourced from the five borewells did not meet the standards of biological tests. Testing revealed the presence of total coliform and Escherichia coli (E. coli) ranging from 8-370 CFU/100 mL and 0-150 CFU/100mL, respectively. According to the requirements of the Regulation of the Minister of Health of the Republic of Indonesia No. 2/MENKES/2023 concerning drinking water quality, the acceptable levels for total coliform and E. coli in drinking water are 0 CFU/100mL. Therefore, the presence of these contaminants in the drilled well water renders it unsuitable for consumption, posing potential health risks to the community.